Interplay of structural chemistry and magnetism in perovskites; a study of CaLn2Ni2WO9; Ln = La, Pr, Nd - Chin, C; Paria Sena, R; Hunter, E; Hadermann, J; Battle, P (Elsevier, 2017)
Polycrystalline samples of CaLn2Ni2WO9 (Ln = La, Pr, Nd) have been synthesized and characterised by a combination of X-ray and neutron diffraction, electron microscopy and magnetometry. Each composition adopts a perovskite-like structure with a ~5.50, b ~5.56, c ~7.78 Å, β ~90.1 ° in space group P21/n. Of the two crystallographically distinct six-coordinate sites, one is occupied entirely (Ln = Pr) or predominantly (Ln = La, Nd) by Ni2+ and the other by Ni2+ and W6+ in a ratio of approximately 1:2. None of the compounds shows long-range magnetic order at 5 K. The magnetometry data show that the magnetic moments of the Ni2+ cations form a spin glass below ~ 30 K in each case. The Pr3+ moments in CaPr2Ni2WO9 also freeze but the Nd3+ moments in CaNd2Ni2WO9 do not. This behaviour is contrasted with that observed in other (A,A’)B2B’O9 perovskites.